2005
DOI: 10.1002/rra.866
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic microbial metabolism in hyporheic sediment of a gravel bar in a small lowland stream

Abstract: Distribution of dissolved oxygen, nitrate, sulphate, carbon dioxide and dissolved organic carbon (DOC), acetate and lactate was studied in the stream and interstitial water along the subsurface flowpath in the hyporheic zone of a small lowland stream. Sediments were found to act as a source of nitrous oxide and methane. Interstitial methane concentrations were significantly much higher in comparison to those from surface water, and were significantly lower in the relatively well oxygenated downwelling zone tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 20 publications
6
26
1
3
Order By: Relevance
“…Similar pathway of methane cycling has been observed by Kuivila et al (1988) in well oxygenated sediments of Lake Washington, however, methane oxidation within the sediments would be rather normal in river sediments compared to lakes. All the above mentioned findings support our previous suggestions that coexistence of various metabolic processes in hyporheic sediments is common due to vertical and horizontal mixing of the interstitial water and occurrence of microbial biofilm (Hlaváčová et al 2005(Hlaváčová et al , 2006.…”
Section: Benthic Fluxes and Potential Methane Oxidationsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar pathway of methane cycling has been observed by Kuivila et al (1988) in well oxygenated sediments of Lake Washington, however, methane oxidation within the sediments would be rather normal in river sediments compared to lakes. All the above mentioned findings support our previous suggestions that coexistence of various metabolic processes in hyporheic sediments is common due to vertical and horizontal mixing of the interstitial water and occurrence of microbial biofilm (Hlaváčová et al 2005(Hlaváčová et al , 2006.…”
Section: Benthic Fluxes and Potential Methane Oxidationsupporting
confidence: 91%
“…Availability of interstitial habitats for bacteria and archaea carrying out anaerobic processes has been confirmed by our previous (Hlaváčová et al 2005(Hlaváčová et al , 2006Cupalová & Rulík 2007) and contemporary findings. During this study we found relatively well developed populations of methanogenic archaea at all localities and that all localities also showed positive methanogenic potential.…”
Section: Occurence Of Methane In Stream Water and Sedimentssupporting
confidence: 74%
See 2 more Smart Citations
“…In fact, stream water downwells into the alluvium in high-head zones and upwells into the stream in low-head zones [20]. Downwelling fluxes carry reactive solutes and DO, which is consumed by the microbial communities within the hyporheic zone [21][22][23][24], resulting in upwelling stream waters with lower DO concentrations than those of stream waters [21,23,[25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%